Customized wire prosthesis (Devise) for alar collapse in sleep apnoea - Singh Nitya; Katyayan Angira; Mishra Anupam; Mishra Pranav; Arvind Kumar Tripathi (Elsevier, 2021)
Background: Alar collapse is known to aggravate snoring-severity and possibly the severity of obstructive sleep apnoea. Various surgical techniques, implants and commercial mechanical/prosthetic nasal alar dilators are evident in literature. Material and methods: A malleable wire prosthesis at 'no' manufacturing cost is custom designed through computer modelling and animation and thereafter tested for its efficacy in 20 normal subjects as per visual analog scale along with its correlation with patient-profiles. Observations and results: All subjects reported improvement in their nasal patency ranging from 30% to 99% but no correlation was seen between the degree of improvement & patient variables. This improvement in normal subjects indicates even a better improvement in true alar collapse. Conclusion: Main advantages of this devise is its extremely low-cost, non-traumatic nature, adjustability to suit patient comfort and can be customised across all types of noses. However it seems cosmetically unacceptable during the daytime, as well as for small children. With no correlation with patient factors the acceptability of this devise is mainly dependent on a good customized design. With a constant use during bedtime in alar collapse this device may not only resolve snoring and improve the sleep-quality of spouse but also enhances oxygenation during sleep.